Investigation of silk sericin conformational structure for fabrication into porous scaffolds with poly(vinyl alcohol) for skin tissue reconstruction. (August 2016) - Yooyod, M.; Ross, G.M.; Limpeanchob, N.; Suphrom, N.; Mahasaranon, S.; Ross, S.
Graphical abstract: Highlights: Effect of storage temperatures on conformational structure of silk sericin. PVA and sericin films that showed random coils had better miscibility than β-sheets. The PVA/RT-SS scaffolds have potential for use in skin-tissue reconstruction scaffolds. Scaffolds with 10% cross-linker (DMU) gave good support for skin fibroblast cells. Abstract: This work is concerned with the study of the conformational structure and crystallinity of sericin from silk cocoon ( Bombyx mori ) and the role these play in the physical and chemical properties of the final materials. Silk sericin (SS) powders were prepared by degumming processes with different storage temperatures before drying into the final powders; defined as RT-SS (room, 25 °C), C-SS (10 °C) and F-SS (freezing, 0 °C), and then fabricated into films and scaffolds by reacting with poly(vinyl alcohol) (PVA) in the presence of a new cross-linker (dimethylolurea; DMU). RT-SS and C-SS structures favour random coil structuring as witnessed by Amide I (CO stretching), II (NH bending) and III (in phase combination of NH in plane-bending and CN stretching vibrations) being observed at 1661, 1538, and 1232 cm −1, respectively. Whereas, F-SS favours β-sheets structure proved by the amide bands shifting to a lower frequency. The NH stretching (3200–2400 cm −1 ) of F-SS is also observed at a lower frequency with a broader band than RT-SS and C-SS due to the hydrogen bonding in the β-sheets. The differences in the X-ray peaks between RT- and C-SS ( d spacing = 1.9–5.2 Å) and F-SS ( d spacing = 3.0 Å and 5.2–8.2 Å) were also measured. Films of PVA/RT-SS/DMU showed better properties than that of PVA/F-SS/DMU films in terms of the interactions (hydrogen bonding) between the components that formed the network. Therefore, RT-SS was chosen for the preparation of 3D porous scaffolds with different concentrations of DMU. All scaffolds showed good support for skin fibroblast cells, as well as promoted cell proliferation. However, a minimal amount of cross-linker, 10% DMU PVA/RT-SS scaffold with average pore diameter between 20 and 30 μm, was the best composition for cell viability and cell adhesion. In this work, therefore, a novel scaffold based on biomaterials was explored for tissue engineering scaffolds with the potential to be a new technology platform for skin tissue regeneration.